Microstructure dependent behavior of the contact interface on porous graphene wrapped Si anodes for Li-ion batteries. (10th March 2023) - Ma, Zhihua; Wang, Cunjing; Li, Aoqi; Wang, Liujie; Chen, Gairong; Miao, Yu; Dang, Tan; Wang, Yunfei; Chang, Enyu; Fan, Tianchao
Highlights: Compact porous Si@graphene layered structure with improved contact interface and adequate interconnected pores were prepared by a facile hydrothermal method. The improved Si/graphene contact interface can promote the positive effect of graphene on restraining the volume change and thus enhance the structural stability during repetitive cycling. The closely wrapping graphene and interconnected pores simultaneously provide adequate paths for fast transfer of electrons and ions, resulting in greatly improved dynamic performance. Abstract: Si/carbon composites are attractive anode materials for rechargeable Li-ion batteries (RLIBs), which combine the advantages of Si and graphene. Designing special Si/carbon structure with intimate contact interface and abundant void space for fast ion transmission is an effective strategy for enhancing cyclability and rate performance of the electrode materials. Inspired by the structure of fishnet, here we fabricate a binder-free and self-standing Si@porous-graphene (Si@PGN60 ) composite with nano silicon particles encapsulated in porous graphene sheets. The obtained Si@PGN60 sample exhibits many favourable features for high performance Si/carbon anodes, including improved Si/graphene contact interface, and abundant void space for fast ion transmission. Tanks to the unique structure, the resultant Si@PGN60 anode presents remarkably improved capacity reaching 1839.9 mA h g −1 at 300 mA g −1, and excellent cycling performance (734 mA h g −1 at a high current density of 3000 mA g −1 ). Graphical abstract: Here we fabricate a binder-free and self-standing Si@graphene (Si@PGN60 ) composite with silicon encapsulated in porous graphene sheets. The obtained Si@PGN exhibits many favourable features for high performance Si/carbon anodes, including improved contact interface between Si and graphene, and abundant void space for fast ion transmission. Tanks to the unique structure, the resultant Si@PGN presents not only remarkably improved capacity reaching 1839.9 mA h g −1 at 300 mA g −1, but also superior rate performance of 734 mA h g −1 at a relatively high current density of 3000 mA g −1 . Image, graphical abstract